Additional cytogenetic abnormalities in chronic myeloid leukemia; an experience from Pakistan - Nida Anwar; Muhammad Nadeem; Sana Khurram; Naveena Fatima; Tahir Shamsi (Journal of the Pakistan Medical Association, 2020)
Objectives: To evaluate the presence and characteristics of additional karyotype abnormalities in chronic myeloid leukaemia cases. Method: The cross-sectional study was conducted at the Department of Cytogenetics and Molecular Pathology, National Institute of Blood Diseases and Bone Marrow Transplant, Karachi, from May 2010 to September 2016 and comprised diagnosed chronic myeloid leukaemiapatients regardless of age and gender.Baseline cytogenetic evaluation was done on overnight, 24-hrs un-stimulated and 72-hrs stimulated bone marrow cultures, and karyotypes were defined according to the International System for Human Cytogenetic Nomenclature2013. Data was analysed using SPSS 23. Results: There were 222 cases with a median age of 38 years (range: 12-84 years). The male-to-female ratio was 1.8:1. Chronic myeloid leukaemiawas detected in 18(8.1%) patients havingadditional cytogenetic abnormalities. Among the patients found positive, cytogenetic type was minor in 10(55.55%), major 3(16.66%), complex 3(16.66%), and variant 2(11.11%). . Conclusion: Additional cytogenetic abnormalitieswere found in 8% of the sample. Key Words: Additional cytogenetic abnormalities, Chronic myelogenous leukaemia, Bone marrow, Cytogenetics. Continuous...